General overview for worldwide trend of fossil fuels - Topal, Erkan; Shafiee, S. (Nova Science Publishers Inc., 2010)
Crude oil, coal and gas, known as fossil fuels, are the main sources of world energy supply. Even though worldwide research has been conducted into other renewable energy resources to replace fossil fuels, the global energy market will continue to depend on fossil fuels, which are expected to satisfy approximately 84% of energy demand in 2030. Views about the reserves of fossil fuels differ. To date there is no scientific consensus on when non-renewable energy will be exhausted. Based on available reserve data and methods, coal will be the only remaining fossil fuel after 2042 and will be available until 2112. The world reserve of fossil fuels mainly depends its consumption and prices. The trend of fossil fuel consumption over the last couple of decades has shown an upward tendency and it is expected to continue until at least 2030. Current predictions indicate that oil will be the main fuel supply of energy until 2030 with a decline in consumption followed by coal and gas. While nominal prices for fossil fuels have followed an escalating trend, real prices have individually fluctuated.Forecasting future fossil fuel prices is uncertain because it is difficult to consider all the significant variables as well as the political implication in a price forecasting models. This chapter individually reviews reserves, demand, supply, and prices of fossil fuels. Subsequently it predicts and comments on the future expectations for fossil fuels as a main source of world energy supply by considering its expected reserves, prices and environmental barriers for their usage.